HUBUNGAN PENGETAHUAN IBU DAN PERILAKU SWAMEDIKASI TERAPI DIARE PADA BALITA DI KLINIK PRATAMA LARAS HATI - Ayu Nur Fatimah; M. Alif Fajri; Aji Tetuko (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2025)
Self-medication is a therapeutic process that involves everything from recognizing symptoms to selecting and using medications. Common or mild illnesses, such as mild fever, mild stomach ache, and diarrhea, are usually treated through self- medication. Diarrhea is a condition involving abnormal or unusual stool production, characterized by an increase in body fluid volume and bowel movement frequency of three times or more. If self-medication is performed improperly, there is a risk of further symptoms arising from the improper use of medications, which can lead to fatal consequences such as death. The purpose of this study is to determine the relationship between mothers' knowledge levels and self-medication behavior for diarrhea in infants at the Laras Hati Sewon Clinic. This study uses an observational method with a descriptive analytical approach and a cross-sectional design, employing simple random sampling as the sampling technique. The sample consisted of 30respondents. The results showed that 77% of mothers at Laras Hati Sewon Primary Clinic had a “good” level of knowledge, 20% had a ‘fair’ level, and 3% had a “poor” level. The level of self-medication behavior among mothers was found to be 64% in the “good” category, 23% in the ‘adequate’ category, and 13% in the “poor” category. The results of the chi-square test analysis showed that there is a relationship between higher education and professional background of mothers, which makes them more effective in managing diarrhea, thereby influencing self-medication behavior in infants, with a p-value < 0.005